Android based Agriculture products price information system - Zuriati Zuriati; Dewi Kania Widyawati (Jurnal Ilmiah ESAI, 2014)
The research is to design the price information system of agriculture products with Android technology basis. The system is useful for the farmers, society or any agribusiness people in getting agriculture product price information. the users are classified according to their accessibility right which are society users that only to access the price information, the users plus group that have the right to provide the price information and the administrator group that have full authority towards the system. The administrator can accept or deny the information provided by the user plus group. The system is developed in accordance with the stages of system/development life cycle (SDLC) through waterfall method. The stages are: analyzing stage to learn the functional and non functional system needs; designing system to design the physical system, logic and interface ; implementing stage that cover the implementing the programming language – Java , and android operating system; assessing stage to assess the system through Black Box testing and; maintaining stage to maintain the system. The assessment result indicates that the system works well; every button designed can function as expected. The test by users also shows that they get the easy access to the information. The users can easily understand the operating manual of the system as it is user frendly and equippped with product pictures visualization. In the future, it is suggested that the system come complete with more agricultural information as horticulture, plantation, fisheries, and livestock.Keywords: Android, Black Box, agriculture product price, informtion system, SDLC